PERILAKU DANA PIHAK KETIGA DALAM MERESPON PERUBAHAN VARIABEL EKONOMI MAKRO PADA BANK UMUM SWASTA NASIONAL (BUSN) PROVINSI JAWA TIMUR PERIODE 2000-2012 - Sangadah, Dhurotus (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2013)
The purpose of this reserach is to knowing of responbility of dependent variabel to exchange of makro economics variable at Excahage Commercial Bank province of East Java. The model analysis is Doubled Linear Regression with employs the OLS (Ordinary Least Square) method. In this research will be used four regression with four dependent variables. In the equation model Saving Deposits, Demand Deposits, Tme Deposits, Third Party Funds are dependent variables and per capita income, interest rate, inflation are independent variables. Result of regression was showed that Saving Deposit more sensitive to respon change of inflations variable that showed by its probability is 0,0024. Time deposit moere sensitive to respon change of interest rates variable taht showed by its probability was 0,0012. Per capita income has same respon of all dependent variable that swowed by its probability was 0,0000